Retinal macrophage-like cell activation and ganglion cell layer thinning are associated with disability and MRI lesion burden in multiple sclerosis - Francesco Pichi; Yanny Perez Jimenez; Matteo Belletti; Alia Alsuwaidi; Fatema Alawadhi; Gina Lee; Piergiorgio Neri; Victoria Mifsud; Anu Jacob; Beatrice Benedetti; Ester Carreño (PLoS ONE, 2026)
Background Multiple sclerosis is a chronic neuroinflammatory disease in which microglia and macrophage-like cells play a central role in disease progression. The retina, as a central nervous system extension accessible to non-invasive imaging, offers a unique window into these processes. Objective The aim of this study was to determine whether retinal macrophage-like cell characteristics and ganglion cell layer thickness are associated with clinical disability and magnetic resonance imaging lesion burden in patients with multiple sclerosis. Methods In this cross-sectional observational study, patients with multiple sclerosis and age-matched healthy controls underwent retinal imaging using spectral-domain optical coherence tomography and swept-source optical coherence tomography angiography. Macrophage-like cells at the vitreoretinal interface were quantified using an automated image-processing pipeline, while ganglion cell layer and retinal nerve fibre layer thicknesses were measured using standardized segmentation. Clinical disability was assessed using the Expanded Disability Status Scale, the 9-Hole Peg Test, and the 25-Foot Walk. Brain magnetic resonance imaging lesion counts were obtained from T1- and T2-weighted sequences. Results Overall retinal macrophage-like cell parameters did not differ between patients with multiple sclerosis and controls. However, patients with greater disability, defined as an Expanded Disability Status Scale score of five or higher, showed significantly increased macrophage-like cell count and density. Macrophage-like cell size demonstrated a moderate positive association with T2 lesion burden, while only weak associations were observed with T1 lesions. Ganglion cell layer thickness was significantly reduced in the inferior and nasal macular regions in patients with multiple sclerosis compared with controls, whereas retinal nerve fibre layer thickness was preserved. Disability scores showed moderate correlations with upper and lower limb functional tests. Conclusions These findings indicate that retinal cellular and structural alterations reflect both inflammatory and neurodegenerative components of multiple sclerosis. Retinal macrophage-like cell metrics are associated with disease burden and disability, while ganglion cell layer thinning provides evidence of neuroaxonal loss. Retinal imaging may serve as a non-invasive complement to magnetic resonance imaging for assessing disease severity and progression in multiple sclerosis.